PENINGKATAN HASIL BELAJAR SISWA PADA MATERI PANCASILA MELALUI MODEL PEMBELAJARAN GAME BASED LEARNING - Rouzatul Jannah, Rouzatul Jannah; Hasanah, Hasanah; Asih Winarty, Asih Winarty (Jurnal Cakrawala, 2024)
The achievement of learning outcomes can be seen from student learning outcomes. Learning will be enjoyable if there is an atmosphere that is relaxed, safe and comfortable, interesting, free from pressure, there is full involvement, an interesting learning environment, enthusiasm, feelings of joy and high concentration. Therefore, a learning model is needed that can improve student learning outcomes. Therefore, the game based learning model is a learning model that is carried out through games by distributing crossword puzzle sheets to each student. The aim of this research is to determine whether the game based learning model using crossword puzzles will improve student learning outcomes on Pancasila material, namely on Pancasila values ​​in everyday life for class X. Data collection in this research was carried out using test questions in the form multiple choice and observation sheet. For student learning outcomes on Pancasila material, the value in the control class with a score of 61.39% is classified as "Fairly effective" criteria. In the experimental class that uses the Game Based Learning learning model, it shows that student learning outcomes have improved with a score of 76.94% belonging to the "Good" criteria. Then the data was tested using the Shapiro-Wilk method and the results had a normal distribution. Next, in the homogeneity of variance test using the F Levene Statistics formula with a sig value. 870 > 0.05 which indicates that the data is homogeneous. The results of the research show that the calculated t value in the Independent Sample t test is greater than the t table, namely 5.315 > 0.000, so H0 is rejected and H1 is accepted, which means there is an increase in student learning outcomes on Pancasila material through the Game Based Learning learning model using crossword puzzles. class X SMA NEGERI 1 INDRAPURI.